Peningkatan Hasil Usaha Tangkapan Nelayan Menggunakan Aplikasi Nelpin (Nelayan Pintar) di Kecamatan Kepulauan Seribu Selatan Provinsi DKI Jakarta - Ganjar Wiryati; Meilani Meilani; Azam Bachur Zaidi (Unri Conference Series: Community Engagement, 2021)
The nelpin application has an impact on the production process of local fishermen. Demonstrating how to use the Nelpin Application is a way to introduce the Nelpin Application to facilitate the fishing process so that it is expected to be more optimal in fishing activities and increase production results. The mentoring was conducted for 3 months from March 8 to June 5, 2021 at KUB Kembung, Tidung Island, South Thousand Islands District, DKI Jakarta Province. The results showed an increase in income of Rp. 309,000 within one month. The demonstration program on how to use the Nelpin application also saw changes in the knowledge aspect by 47.2%, and the attitude aspect increased by 18.2%, which initially agreed to strongly agree, as well as the skill aspect where the average member obtained was quite therapist to be skilled. The impact of using the Nelpin Application is that the average yield of fishermen's production increases by 7.7% which affects fishermen's income. In the calculation of business analysis carried out on average, fishermen found BEP = 39.8 Units, PP = 1.32, RC = 2.6 with a selling price of Rp. 25,000, and the income earned is Rp. 4,309,000 with a profit of Rp. 309,000, with a total production cost of Rp. 1,644,999/month.